Electrolytic copper foil for secondary batteries and its manufacturing method
By using TOC, zinc, and iron in specific ratios in the plating solution, the electrolytic copper foil stabilizes grain sizes and crystal structures, addressing the issue of high-temperature vacuum drying-induced changes, thereby improving battery life and preventing cracks.
Patent Information
- Application Number
- JP2021163961
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2016-11-11
- Filing Date
- 2021-10-05
- Publication Date
- 2025-02-04
- Estimated Expiration
- 2037-03-28
AI Technical Summary
Existing electrolytic copper foils used in secondary batteries face issues with changes in grain sizes and crystal structures during high-temperature vacuum drying, leading to reduced battery life and performance due to changes in adhesion and stress with the coating surface, which can cause cracks.
Incorporating Total Organic Carbon (TOC), zinc, and iron in specific ratios into the plating solution to stabilize grain sizes and crystal structures, maintaining tensile strength and extension rates within certain ranges to prevent physical property changes during high-temperature vacuum drying.
The solution effectively minimizes grain size and crystal structure changes, enhancing battery cycle life and preventing cracks, thus maintaining battery performance and longevity.
Smart Images

Figure 0007626309000004 
Figure 0007626309000005 
Figure 0007626309000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrodeposited copper foil for a secondary battery and a manufacturing method thereof, and more particularly, to an electrodeposited copper foil for a secondary battery, which has little change in physical properties before and after vacuum drying during the manufacturing process of the electrodeposited copper foil, has excellent cycle life when tested with a high-density cathode, and is capable of preventing the occurrence of cracks, and a manufacturing method thereof. [Background technology]
[0002] In general, electrolytic copper foil is widely used as a basic material for PCBs (Printed Circuit Boards) in the electrical / electronics industry, and demand is rapidly increasing, especially for small products such as slim notebook computers, personal digital assistants (PDAs), e-books, MP3 players, next-generation mobile phones, ultra-thin flat panel displays, etc. In addition, by improving the physical properties of electrolytic copper foil, it is also widely used as a cathode current collector for secondary batteries.
[0003] Typically, electrolytic copper foil is produced by electrolysis in an electrolytic cell that includes a cylindrical titanium cathode (also called a drum), a titanium anode coated with a lead alloy or iridium oxide that is spaced apart from the cathode, an electrolyte, and a current source. The electrolyte is made of sulfuric acid and / or copper sulfate, and when a direct current is passed between the cathode and the anode while the cylindrical cathode is rotated, copper is electrodeposited on the cathode, making it possible to continuously produce electrolytic copper foil. The process of reducing copper ions to metal by electrolysis in this way is called the foil-making process.
[0004] The copper foil obtained in the foil manufacturing process can then be subjected to additional surface treatment processes, such as a nodule treatment process to improve adhesion to the insulating substrate, a diffusion prevention process to prevent the diffusion of copper ions, an anti-rust treatment to prevent oxidation from the outside, and a chemical adhesion improvement process to complement adhesion to the insulating substrate, if necessary. If the surface treatment process is performed, it becomes copper foil for low-profile printed circuits, and if only the anti-rust treatment is performed among the surface treatment processes, it becomes copper foil for secondary batteries.
[0005] When electrodeposited copper foil is used for printed circuits, it is supplied to PCB processors in a laminated form with an insulating substrate after surface treatment, whereas when it is used for secondary batteries, it is supplied to secondary battery manufacturers after only undergoing anti-rust treatment.
[0006] When the electrolytic copper foil is used as a cathode current collector for a secondary battery, both sides of the copper foil are coated with an electrode active material. In this case, if the roughness of both sides of the electrolytic copper foil is different, the battery characteristics will be different, so it is necessary to maintain the roughness of both sides of the electrolytic copper foil to be the same or at a similar level.
[0007] In the manufacturing process of secondary batteries using these electrolytic copper foils, a step of vacuum drying the copper foil is performed. However, since vacuum drying is a process that is performed at high temperature for a long time, there is a problem that the adhesive strength and stress between the copper foil and the coating surface of the active material change during the step of vacuum drying the copper foil, which reduces the battery life or generates cracks.
[0008] Therefore, there is a demand for an electrodeposited copper foil for secondary batteries that can minimize changes in physical properties even after being left at high temperatures for a long time so as not to affect the life and performance of the battery even after a vacuum drying process. Summary of the Invention [Problem to be solved by the invention]
[0009] The present invention relates to an electrodeposited copper foil for a secondary battery, which can improve the life of the battery by minimizing changes in grain size and crystal structure by making TOC and metal additives, zinc and iron, present in a certain content in a copper electrolyte, and a manufacturing method thereof.
[0010] The present invention also relates to an electrodeposited copper foil for a secondary battery, which can minimize changes in physical properties of the copper foil even after vacuum drying during the production of the electrodeposited copper foil, thereby improving the cycle life and characteristics of the battery and preventing the occurrence of cracks, and a method for producing the same. [Means for solving the problem]
[0011] According to one aspect of the present invention, an embodiment of the present invention is an electrolytic copper foil for a secondary battery, which is manufactured by using a drum of a plating solution containing TOC (total organic carbon), zinc, and iron, and the ratio of TOC, zinc, and iron contained in the electrolytic copper foil satisfies the following formula 1:
[0012] Equation 1: TOC / (Zn+I)=1.3-1.5 The electrolytic copper foil is vacuum-dried after being coated with a negative electrode active material, and the ratio of the tensile strength and elongation rate before and after the vacuum drying is characterized by satisfying the following formula 2.
[0013] Equation 2: ((tensile strength after vacuum drying / tensile strength before vacuum drying) / (stretching rate after vacuum drying / stretching rate before vacuum drying)) × tensile strength after vacuum drying = 28~50 The tensile strength before and after the vacuum drying is characterized by complying with the following formula 3.
[0014] Equation 3: Tensile strength after vacuum drying / Tensile strength before vacuum drying = 0.8~1.01 The stretching ratio before and after the vacuum drying is characterized in that it satisfies the following formula 4.
[0015] Equation 4: Stretching ratio after vacuum drying / stretching ratio before vacuum drying=0.9~1.4 The plating solution is characterized in that the concentration of TOC contained therein is 100 ppm or more.
[0016] The room temperature tensile strength of the electrolytic copper foil is 40 kgf / mm 2 ~51kgf / mm 2 It is characterized in that:
[0017] The electrolytic copper foil has a thickness of 4 μm to 12 μm.
[0018] The electrolytic copper foil has a stretch ratio of 2% to 18%.
[0019] According to one aspect of the present invention, an embodiment of the present invention is a method for producing an electrolytic copper foil for a secondary battery, comprising the steps of: (1) preparing a plating solution containing copper, TOC, zinc and iron; (2) performing electrolytic plating using a drum at a temperature of 30°C to 70°C and a current density of 30 ASD to 150 ASD; and (3) vacuum drying the electrolytic copper foil formed by the electrolytic plating, wherein the ratio of TOC, zinc and iron contained in the electrolytic copper foil satisfies the following formula 1:
[0020] Equation 1: TOC / (Zn+I)=1.3-1.5 The ratio of the tensile strength and the elongation rate before and after the vacuum drying is characterized by satisfying the following formula 2.
[0021] Equation 2: ((tensile strength after vacuum drying / tensile strength before vacuum drying) / (stretching rate after vacuum drying / stretching rate before vacuum drying)) × tensile strength after vacuum drying = 28~50 The plating solution is characterized in that the concentration of TOC contained therein is 100 ppm or more.
[0022] The room temperature tensile strength of the electrolytic copper foil is 40 kgf / mm 2 ~51kgf / mm 2 It is characterized in that:
[0023] The electrolytic copper foil has a thickness of 4 μm to 12 μm.
[0024] The electrolytic copper foil has a stretch ratio of 2% to 18%. Effect of the Invention
[0025] According to the present invention, the TOC and the metal additives, zinc and iron, are present in a constant content in the copper electrolyte, thereby minimizing changes in grain size and crystal structure and improving the battery life.
[0026] In addition, according to the present invention, during the production of the electrolytic copper foil, even after vacuum drying, the change in physical properties of the copper foil can be minimized, the cycle life and characteristics of the battery can be improved, and the occurrence of cracks can be prevented. [Brief description of the drawings]
[0027] [Figure 1] 1 is a flowchart showing a method for producing an electrolytic copper foil for a secondary battery according to an embodiment of the present invention. [Diagram 2] 1 is a diagram showing a process for manufacturing an electrolytic copper foil using a drum according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0028] Further details of the embodiments are included in the detailed description and the drawings.
[0029] The advantages and features of the present invention, and the methods for achieving them, will become clear with reference to the following detailed description of the embodiments in conjunction with the accompanying drawings. However, the present invention is not limited to the embodiments disclosed below, and may be embodied in various different forms. In the following description, when a part is connected to another part, this includes not only a direct connection, but also a connection via another medium. In addition, in the drawings, parts that are not related to the present invention are omitted to clarify the description of the present invention, and similar parts are designated by the same reference numerals throughout the specification.
[0030] The present invention will now be described with reference to the accompanying drawings.
[0031] Next, the electrolytic copper foil for a secondary battery according to an embodiment of the present invention will be described in more detail.
[0032] According to an embodiment of the present invention, the electrodeposited copper foil for a secondary battery is manufactured by using a drum, and the electrodeposited copper foil is vacuum-dried after being coated with a negative electrode active material, and the ratio of the tensile strength and the elongation rate before and after the vacuum drying may be expressed by the following formula 2:
[0033] Equation 2: ((tensile strength after vacuum drying / tensile strength before vacuum drying) / (stretching rate after vacuum drying / stretching rate before vacuum drying)) × tensile strength after vacuum drying = 28~50 In addition, the tensile strength before and after the vacuum drying can be expressed by the following formula 3, and the stretch ratio before and after the vacuum drying can be expressed by the following formula 4.
[0034] Equation 3: Tensile strength after vacuum drying / Tensile strength before vacuum drying = 0.8~1.01 Equation 4: Stretching ratio after vacuum drying / stretching ratio before vacuum drying=0.9~1.4 When the electrolytic copper foil is vacuum dried in the manufacturing process of the battery, if the electrolytic copper foil is left at high temperature for a long time, the grain size and crystal structure of the electrolytic copper foil change, which later causes detachment of the active material and cracks during charging and discharging of the battery, shortening the life of the battery. Therefore, in order to ensure excellent battery life, the change in the physical properties of the electrolytic copper foil must be minimized even after vacuum drying.
[0035] In the present invention, in order to minimize changes in the physical properties of the copper foil even after vacuum drying, the TOC content in the copper electrolyte is set to 100 ppm or more, so that abnormal growth of grain size and changes in crystal structure can be prevented even if the copper foil is vacuum dried at high temperature for a long time.
[0036] TOC is an abbreviation of Total Organic Carbon, which means the total amount of organic carbon in the plating solution, and is included in the copper electrolyte to reduce the grain size. If the copper electrolyte contains dissolved carbon dioxide (TIC) (total inorganic carbon) that is not TOC, or carbon adsorbed to copper ions, the additives in the grains will diffuse to the grain boundaries when the copper electrolyte is left at high temperature for a long time after vacuum drying, causing abnormal grain growth and changes in the crystal structure. The physical property changes of the copper foil shown above after vacuum drying can change the adhesive strength and stress with the coating surface of the active material, which can cause the active material to detach and crack when the battery is charged and discharged.
[0037] Therefore, in the present invention, the TOC is made to be present in the copper electrolyte at 100 ppm or more, and after vacuum drying, the physical property changes of the copper foil are prevented and optimized, and the cycle life and characteristics can be improved when the battery is tested with a high density cathode.
[0038] The ratio between the tensile strength and the elongation before and after the vacuum drying of the electrodeposited copper foil for secondary battery according to the present invention is preferably within the range of the above formulas 2 to 4. If the tensile strength and the elongation before and after the vacuum drying are out of the above ranges, the adhesive strength and stress between the copper foil and the active material coating surface may change, and the battery performance may be deteriorated.
[0039] FIG. 1 is a flow chart showing a method for producing an electrodeposited copper foil for a secondary battery according to an embodiment of the present invention. Referring to FIG. 1, the method for producing an electrodeposited copper foil for a secondary battery according to the present invention includes: (1) adding copper ions (Cu 2+(1) preparing a plating solution containing 60 g / L to 140 g / L of cadmium, 70 g / L to 200 g / L of sulfuric acid, 10 ppm to 90 ppm of chlorine, 100 ppm or more of TOC, and zinc and iron as metal additives (S100); (2) applying a current density of 30 ASD to 150 ASD under conditions of a temperature of 30°C to 70°C and performing electrolytic plating using a drum (S200); and (3) vacuum drying the electrolytic copper foil formed by the electrolytic plating (S300).
[0040] In step (1) (S100), a plating solution is prepared by adding copper ions (Cu 2+ A plating solution containing 60 g / L to 140 g / L of cadmium, 70 g / L to 200 g / L of sulfuric acid, 10 ppm to 90 ppm of chlorine, 100 ppm or more of TOC, and zinc and iron as metal additives is prepared. In the plating solution, TOC plays a role in minimizing changes in grain size and crystal structure of the electrolytic copper foil even if the electrolytic copper foil is kept at high temperature for a long time in the vacuum drying step performed after the production of the electrolytic copper foil. In the present invention, the plating solution contains 100 ppm or more of TOC to produce the electrolytic copper foil, thereby minimizing changes in grain size and crystal structure even if the electrolytic copper foil is left at high temperature for a long time during vacuum drying, and preventing detachment and cracking of active materials during later charging and discharging of the battery.
[0041] In addition, in the present invention, in order to minimize the change in physical properties of the electrolytic copper foil after vacuum drying, zinc and iron are further included as metal additives in addition to TOC. The electrolytic copper foil can be manufactured by electrolytic plating using a plating solution, in which TOC can be included at a certain content, zinc can be included at 50 mg / L to 700 mg / L, and iron can be included at 400 mg / L to 1100 mg / L.
[0042] In the electrolytic copper foil formed by electrolytic plating using a plating solution containing TOC, zinc, and iron, the TOC content is preferably 100 ppm or more, and the zinc and iron contents may be provided to correspond to the following formula 1:
[0043] When the electrolytic copper foil is produced by electrolytic plating, the concentrations of additives, such as TOC, zinc, and iron, contained in the plating solution are not always the same as those of the electrolytic copper foil produced by electrolytic plating, but may be the same or less.
[0044] The zinc and iron adjust the plating speed of copper during electrolytic plating, flatten the surface of the electrolytic copper foil, and prevent the carbon content in the electrolytic copper foil from increasing excessively. Therefore, when the ratio of zinc, iron, and TOC in the electrolytic copper foil is within the range of the following formula 1, the change in physical properties of the electrolytic copper foil after vacuum drying is minimized.
[0045] Equation 1: TOC / (Zn+I)=1.3-1.5 If the ratio is less than 1.3, the content of zinc and iron added to the plating solution increases, suppressing the effect of TOC in the plating solution in preventing abnormal grain growth, which is undesirable, and if the ratio exceeds 1.5, stress occurs in the grains due to the excessive TOC content in the electrodeposited copper foil, and if the electrodeposited copper foil is exposed to high temperatures during vacuum drying, the grains in the electrodeposited copper foil may grow abnormally, causing serious changes in physical properties after vacuum drying. Therefore, in order to minimize changes in grain size and crystal structure even when exposed to high temperatures for a long time, it is preferable to maintain the ratio of TOC, zinc, and iron in the range of 1.3 to 1.5 as shown in formula 1.
[0046] If the copper ions and sulfate ions in the plating solution are outside the above ranges, copper foil may not be properly deposited during subsequent electrolytic plating, or the hardness of the copper foil may be reduced.
[0047] In addition, the plating solution contains 10 ppm to 90 ppm of chlorine, and chlorine suppresses crystal growth when CuCl2 precipitates formed at grain boundary interfaces during electrolytic plating are heated to high temperatures, thereby improving thermal stability at high temperatures. If the chlorine concentration is out of the range of 10 ppm to 90 ppm, the tensile strength of the electrolytic copper foil may decrease, and the thermal stability at high temperatures may decrease.
[0048] In step (2) (S200), the plating solution prepared in step (1) is electroplated using a drum at a temperature of 30° C. to 70° C. and a current density of 30 ASD (Ampere per Square Decimal) to 150 ASD. FIG. 2 is a diagram showing the steps of manufacturing an electrolytic copper foil using a drum according to an embodiment of the present invention. If the plating temperature and current density are outside the above-mentioned ranges, plating may not be performed normally, the surface of the electrolytic copper foil may not be uniform, or the tensile strength and elongation rate may be reduced, which may cause a deterioration in battery performance.
[0049] Step (3) (S300) includes a step of vacuum drying the electrolytic copper foil formed by the electrolytic plating. The vacuum drying is preferably performed at a temperature in the range of 110°C to 150°C for 6 to 10 hours. If the vacuum drying temperature is outside the above range, the electrolytic copper foil may not be dried normally or may be deformed due to high temperature. In addition, if the vacuum drying time is less than 6 hours, the electrolytic copper foil may not be dried completely, and if the drying time exceeds 10 hours, the performance of the electrolytic copper foil may be deteriorated due to excessive drying.
[0050] The room temperature tensile strength of the electrolytic copper foil for secondary batteries according to the present invention is 40 kgf / mm 2 ~51kgf / mm 2 It is preferable that the tensile strength is 40 kgf / mm 2 If it is less than 40kgf / mm, the electrolytic copper foil may break, causing a short circuit between the anode and cathode. When the secondary battery is charged and discharged, the volume of the secondary battery expands or contracts as other active materials such as graphite exchange lithium ions. At this time, the active material layer is in close contact with the electrolytic copper foil, so stress is generated due to the expansion or contraction. Therefore, the tensile strength is 40kgf / mm 2 If the thickness is less than 100 mm, the electrolytic copper foil cannot withstand the stress and is broken, making it impossible to maintain the battery performance, and the breakage may cause deformation, resulting in a short circuit between the anode and the cathode.
[0051] In addition, the thickness of the electrolytic copper foil for secondary batteries according to the present invention is preferably 4 μm to 12 μm. If the thickness of the electrolytic copper foil is less than 4 μm, the electrolytic copper foil may be easily broken due to its thin thickness, and if the thickness of the electrolytic copper foil is more than 12 μm, the volume and weight of the secondary battery to be manufactured increases, which is not preferable.
[0052] In addition, the elongation ratio of the electrolytic copper foil for secondary batteries according to the present invention is preferably 2% to 18%. When the elongation ratio of the electrolytic copper foil is high, it has an advantage that it can withstand tension during coating of active materials in the electrode manufacturing process, and can prevent breakage during the process, and can prevent breakage due to stress received during the electrode winding process. In addition, it prevents efficiency reduction and breakage during the charge / discharge cycle of the battery, improving the performance of the battery. However, if the elongation ratio exceeds 18%, the secondary battery may be severely deformed and short-circuited during charge / discharge, and if the elongation ratio is less than 2%, the electrolytic copper foil may easily break.
[0053] The tensile strength and elongation ratio are inversely proportional to each other, that is, when the tensile strength increases, the elongation ratio decreases, and when the tensile strength decreases, the elongation ratio increases. Therefore, in order to manufacture an electrodeposited copper foil having high tensile strength while preventing breakage, it is important to maintain the tensile strength and elongation ratio within the appropriate range. Therefore, the tensile strength is 40 kgf / mm 2 ~51kgf / mm 2 It is preferable to maintain the elongation ratio in the range of 2% to 18% in order to prevent short circuit between the anode and cathode when the secondary battery is deformed.
[0054] Hereinafter, examples and comparative examples of the present invention will be described. However, the following examples are only preferred examples of the present invention, and the scope of the present invention is not limited to the following examples.
[0055] Battery life test with TOC concentration and physical property changes before and after vacuum drying *(Example 1) A plating solution containing 90g / L copper ions, 120g / L sulfuric acid, 30ppm chlorine, 360ppm TOC, 0.375g / L zinc, and 0.75g / L iron (total of zinc and iron: 0.243g / L) was prepared, and electrolytic plating was performed using a drum at 55°C and a current density of 90ASD. The electrolytic copper foil formed by electrolytic plating was then vacuum dried at 120°C for 7 hours.
[0056] (Examples 2 to 8) The plating solution was prepared in the same manner as in Example 1, except that the concentrations of TOC, zinc and iron contained in the plating solution were as shown in Tables 2 and 3 below.
[0057] (Comparative Examples 1 to 3) In Comparative Examples 1 to 3, electrolytic copper foils were manufactured under the same conditions as in Example 1, except that the concentrations of TOC, zinc and iron in the plating solutions were as shown in Tables 2 and 3 below.
[0058] The experimental conditions of Examples 1 to 8 and Comparative Examples 1 to 3 were the same as those described above. The tensile strength and elongation before and after vacuum drying, the percentage of TOC, zinc, and iron after melting the copper foil, and the battery life after 300 cycles of each of the electrodeposited copper foils for secondary batteries prepared by the above methods were measured and are shown in Tables 2 and 3 below.
[0059] Tensile strength and elongation were measured by cutting tensile test pieces of 12.7 mm width × 50 mm gauge length from the electrodeposited copper foils obtained in Examples 1 to 8 and Comparative Examples 1 to 3, and carrying out a tensile test at a crosshead speed of 50.8 mm / min according to the IPC-TM-6502.4.18B standard. The maximum load of the tensile strength was defined as the tensile strength, and the elongation at break was defined as the elongation.
[0060] In addition, the percentages of TOC, zinc, and iron after dissolving the copper foil were analyzed by dissolving the electrolytic copper foils obtained in Examples 1 to 8 and Comparative Examples 1 to 3 in 60 ml of hydrochloric acid (35%) and 40 ml of hydrogen peroxide (30%) using ICP (Inductively Coupled Plasma Mass Spectrometry). The percentages of TOC, zinc, and iron were calculated using Equation 1, and the results are shown in Table 3 below.
[0061] The battery evaluation conditions were set as follows, and the cell design, anode, cathode, separator, and electrolyte conditions were set as shown in Table 1 below.
[0062] 1) Constant current charging: current value 1C, charge end voltage 4.2V 2) Rest for 20 minutes 3) Constant current discharge: current value 1C, charge cut-off voltage: 2.5V cut off 4) 1C=487mAh 5) Cycle: 300 cycles, Temperature: 55℃
[0063] [Table 1] JPEG0007626309000002.jpg127141 JPEG0007626309000003.jpg169147Referring to Tables 2 and 3, it can be seen that in Comparative Example 1 to Comparative Example 3, in which the TOC concentration is less than 100 ppm, the ratios of the tensile strength and elongation ratio of Equation 2 before and after vacuum drying are all less than 28, while in Examples 1 to 8, in which the TOC concentration is more than 100 ppm, the ratios of the tensile strength and elongation ratio of Equation 2 before and after vacuum drying are all in the range of 28 to 50. During the manufacture of electrolytic copper foil, vacuum drying is performed at a high temperature of 100° C. or more for a long time, so that the grain size and crystal structure in the electrolytic copper foil may change due to the high temperature, and such changes in the physical properties of the electrolytic copper foil may cause a decrease in the life of the battery. TOC plays a role in preventing changes in the physical properties of the electrolytic copper foil, and when the TOC is maintained at 100 ppm or more as in Examples 1 to 8, the changes in the physical properties are small even after the high-temperature vacuum drying process, and therefore the life of the battery is excellent.
[0064] In addition, in Comparative Examples 1 to 3, in which the ratios of TOC / (Zn+Fe) were all less than 1.3, it was found that the changes in physical properties before and after vacuum drying were greater than those in Examples 1 to 8, and the battery life was also very short. When the ratio of TOC / (Zn+Fe) was less than 1.3, the content of the metal additive increased, and the TOC in the plating solution failed to prevent the abnormal growth of grains, which seems to cause a significant change in the physical properties of the electrolytic copper foil after vacuum drying.
[0065] In addition, the batteries according to Examples 1 to 8 and Comparative Examples 1 to 3, whose capacities after 300 cycles were confirmed from Table 3, were disassembled to check the state of the electrolytic copper foil (which acted as a negative electrode plate). At this time, it was confirmed that the electrolytic copper foils according to Examples 1 to 8 had no defective appearance and were the same as the original. Meanwhile, in the cases of Comparative Examples 1 to 3, it was confirmed that a part of the electrolytic copper foil was broken or peeled off, in the case of Comparative Example 1, it was confirmed that there was a part where the negative electrode active material was peeled off from the electrolytic copper foil, and in Comparative Examples 2 and 3, it was confirmed that a broken part was formed on the outer part of the electrolytic copper foil.
[0066] Those skilled in the art will understand that the present invention can be implemented in other specific forms without changing its technical idea or essential features. Therefore, it should be understood that the above-described embodiments are illustrative in all respects and not limiting. The scope of the present invention is defined by the claims below rather than the above detailed description, and all modifications or variations derived from the meaning and scope of the claims and their equivalents should be interpreted as being included in the scope of the present invention.
Claims
1. An electrolytic copper foil for a secondary battery, comprising TOC (total organic carbon), zinc and iron, and formed by electrolytic plating using a plating solution, The ratio of TOC, zinc and iron contained in the electrolytic copper foil measured after dissolving the electrolytic copper foil is calculated according to the following formula 1: TOC / (zinc + iron) = 1.3 to 1.5 and the TOC concentration in the plating solution is 450 to 1080 ppm. An electrolytic copper foil for a secondary battery, The electrolytic copper foil for a secondary battery, wherein the plating solution contains 50 mg / L to 700 mg / L of zinc and 400 mg / L to 1100 mg / L of iron.
2. The electrolytic copper foil is vacuum-dried after being coated with a negative electrode active material, and the ratio of the tensile strength and the elongation rate before and after the vacuum drying of the electrolytic copper foil coated with the negative electrode active material is expressed by the following formula 2: ((tensile strength after vacuum drying / tensile strength before vacuum drying) / (stretch rate after vacuum drying / stretch rate before vacuum drying))×tensile strength after vacuum drying=28 to 50 2. The electrolytic copper foil for a secondary battery according to claim 1, wherein the vacuum drying is carried out at a temperature in the range of 110° C. to 150° C. for 6 hours to 10 hours.
3. The electrolytic copper foil is vacuum-dried after coating with a negative electrode active material, and the tensile strength before and after the vacuum drying is expressed by the following formula 3: Tensile strength after vacuum drying / Tensile strength before vacuum drying = 0.8 to 1.01 2. The electrolytic copper foil for a secondary battery according to claim 1, wherein the vacuum drying is carried out at a temperature in the range of 110° C. to 150° C. for 6 hours to 10 hours.
4. The electrolytic copper foil is vacuum-dried after coating with a negative electrode active material, and the elongation ratio before and after the vacuum drying is expressed by the following formula 4: Stretching ratio after vacuum drying / stretching ratio before vacuum drying=0.9 to 1.4 The electrolytic copper foil for a secondary battery according to claim 1 .
5. The room temperature tensile strength of the electrolytic copper foil is 40 kgf / mm 2 ~51kgf / mm 2 The electrolytic copper foil for secondary batteries according to claim 1 ,
6. The electrolytic copper foil for a secondary battery according to claim 1, wherein the thickness of the electrolytic copper foil is 4 μm to 12 μm.
7. The electrolytic copper foil for a secondary battery according to claim 1, wherein the elongation ratio of the electrolytic copper foil is 2% to 18%.
Citation Information
Patent Citations
Copper alloy foil current collector for secondary battery
JP1999339811A
Anode material for lithium ion battery
JP2006049237A
Electrolytic copper foil and negative electrode collector for secondary battery
JP2013181236A
Electrolytic copper foil, and secondary battery collector and secondary battery using the same
JP2014037583A
Surface-treated copper foil, copper foil with carrier, printed wiring board, copper-clad laminate, laminate and method for producing printed wiring board
WO2015108191A1